Pengaruh Modul Interaktif Terintegrasi ESD terhadap Minat Belajar dan Keterampilan Berpikir Kreatif Peserta Didik Kelas VII SMPN 23 Pekanbaru - Rahmah Tika Syurya; Hadi Purwanto; Defrizal Hamka; Widodo Widodo (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The effect of the integrated interactive Education for Sustainable Development (ESD) module on learning interest and creative thinking skills of class VII students at SMPN 23 Pekanbaru was the focus of this study. One of the learning resources that is particularly suitable for the 21st century is interactive modules. These modules serve as detailed learning packages designed to help students achieve their learning objectives. The Education for Sustainable Development (ESD) approach used in this study aims to not only increase students' interest and readiness to learn but also enhance their creative thinking skills. The purpose of this research was to examine and analyze the effect of the integrated interactive ESD module on learning interest and creative thinking skills, and to describe the correlation between learning interest and creative thinking skills in students. The study employed a quasi-experimental design combined with correlation analysis, using instruments such as a learning interest questionnaire and a creative thinking skills test. The findings of the study indicated that the integrated interactive ESD module had a significant effect on both the learning interest and the creative thinking skills of students. Furthermore, there was a positive correlation between learning interest and creative thinking skills, suggesting that enhancing students' engagement in the learning process through interactive modules can foster the development of their creative thinking abilities. These results highlight the importance of interactive learning resources in supporting student achievement in the 21st century